The Synergy of the Three Pillars of Education in Early Childhood Character Education - Kuswanto, Anggil Viyantini; Wibowo, Devi Vionitta; Setiawati, Feby Atika (Universitas Islam Negeri Raden Intan Lampung, 2023)
Lack of communication, prejudice, and cooperation that occurs internally becomes an obstacle in building children's character. This study aims to inform about the synergy of the three pillars of education in building character education in early childhood. The research method uses inductive qualitative research. The subjects of this study included RA teachers, parents, and the community involved in activities. Data analysis uses source triangulation. The research results obtained that by increasing roles, strategies, and collaboration between schools, parents, and the community, such as starting good communication, fostering trust and collaboration, setting group norms with full awareness, supporting school programs by fulfilling children's rights, and actively and passively support and assist in the form of personnel, ideas, financial contributions, and materials and support learning activities.